Theoretical Investigation of Terahertz Spoof Surface-Plasmon-Polariton Devices Based on Ring Resonators - Can Liu; Shenghao Gu; Mingming Sun; Ya Liu; Ying Zhang; Jiaguang Han (Photonics)
Terahertz is one of the most promising technologies for high-speed communication and large-scale data transmission. As a classical optical component, ring resonators are extensively utilized in the design of band-pass and frequency-selective devices across various wavebands, owing to their unique characteristics, including optical comb generation, compactness, and low manufacturing cost. While substantial progress has been made in the study of ring resonators, their application in terahertz surface wave systems remains less than fully optimized. This paper presents several spoof surface plasmon polariton-based devices, which were realized using ring resonators at terahertz frequencies. The influence of both the radius of the ring resonator and the width of the waveguide coupling gap on the coupling coefficient are investigated. The band-stop filters based on the cascaded ring resonator exhibit a 0.005 THz broader frequency bandwidth compared to the single-ring resonator filter and achieve a minimum stopband attenuation of 28 dB. The add–drop multiplexers based on the asymmetric ring resonator enable selective surface wave outputs at different ports by rotating the ring resonator. The devices designed in this study offer valuable insights for the development of on-chip terahertz components.